Explanatory Risk Factors for Psychopathic Symptoms in Men and Women: Results from Generation 3 of the Cambridge Study in Delinquent Development - Farrington, David (Journal of developmental and life-course criminology, 2023)
Risk factors are central to the understanding and prediction of psychopathology. The current study focuses on risk factors for psychopathic personality and psychopathic behaviour by investigating the following: (1) Early risk factors for later psychopathic personality and psychopathic behaviour in men and women, and (2) Independently predictive risk factors for later psychopathic personality and psychopathic behaviour in men and women. The study analyses data from the third generation (Generation 3; “G3) of the Cambridge Study in Delinquent Development (CSDD). The G3 consists of both men (N = 291) and women (N = 260), and the results indicate that there are clear similarities in explanatory risk factors (e.g., risk taking and poor supervision) between men and women. There are however some important differences as it seems that attachment and socialisation factors are more important for women, and early school leaving is more important for men. Implications for early interventions are discussed.